Engineering Tomorrow: Optimised Materials and Surfaces for Additive Manufacturing - Raša Urbas; Marina Vukoje; Tomislav Cigula (Applied Sciences)
Focusing on advancements in additive manufacturing, this Special Issue explores the role of novel materials and surface technologies in improving functionality, performance, and sustainability. The research papers highlight innovative approaches to understanding and overcoming material limitations, particularly in the areas of surface engineering, process optimisation, and multi-material applications. Key topics include the tribological behaviour, wear resistance, and surface quality of coated components, the effects of process parameters on mechanical strength and surface roughness, and advanced methods for surface characterisation and quality control. By addressing challenges, such as material efficiency, friction reduction, and structural integrity, the researchers emphasise the crucial role of novel materials and technologies to push the boundaries of additive manufacturing. Looking to the future, integrated strategies that prioritise sustainability, material innovation, and application-driven optimisation will be crucial. Through collaboration and technological advancement, this Special Issue provides valuable insights that will contribute to a more efficient, sustainable, and versatile future of additive manufacturing.